Plasmonic-Enhanced Infrared Absorption Platform for Broadband and Multiple Molecular Fingerprint Retrieval - Yulong Hu; Zexing Zheng; Huishan Ma; Shuguang Zhu; Yiming Yu; Jie Hong; Weiwei Tang; Jiale He; Libo Zhang; Changlong Liu; Guanhai Li; Xiaoshuang Chen (Nanomaterials)
The mid-infrared (mid-IR) region, often referred to as the molecular fingerprint region, encompasses the distinctive absorption spectra characteristic of numerous important molecules. However, the intrinsically small molecular absorption cross-sections, combined with the size mismatch between nanoscale molecules and microscale mid-IR wavelengths, result in inherently weak light-molecule interactions. In this work, we propose a broadband, tunable platform based on plasmonic-enhanced infrared absorption for label-free retrieval of molecular fingerprints. By leveraging the strong near-field enhancement of the plasmonic structure, the platform significantly amplifies light-molecule interactions, enabling precise reconstruction of the fingerprint absorption spectra of target molecules. In addition, the proposed structure exhibits exceptional molecular detection capabilities across the wavelength range of 5–10 μm, with remarkable potential for distinguishing molecular mixture components. The results pave the way for the applications in chemical identification, biomedical diagnostics, environmental monitoring, and other interdisciplinary fields, which require miniaturized and high-precision sensing.